Metode Kombinasi Menurunkan Kadar BOD5 dan COD Limbah Cair Tepung Aren - Nirwana, Rahina Esti; Windraswara, Rudatin (HIGEIA (Journal of Public Health Research and Development), 2020)
ABSTRAK Limbah cair tepung aren merupakan limbah yang dihasilkan pada proses pemerasan serat aren untuk mendapatkan endapan tepung pati. Limbah yang dihasilkan mengandung kadar BOD5 2985 mg/L dan COD 8740 mg/L yang melebihi baku mutu menurut Perda Jateng No 5 tahun 2012. Tujuan penelitian untuk mengetahui penurunan kadar BOD5 dan COD dengan metode kombinasi aerasi filtrasi dan adsorpsi. Jenis penelitian yang digunakan adalah eksperimen dengan pendekatan Pretest-Posttest Control Group Design. Jumlah replikasi yang digunakan sebanyak 4. Data dianalisis menggunakan uji T-test berpasangan. Tidak terdapat perbedaan bermakna kadar BOD5 sebelum dan sesudah perlakuan pada treatment 1 (0,052), treatment 2 (0,057), treatment 3 (0,138), kontrol (0,964) (p>0,05). Terdapat perbedaan bermakna kadar COD sebelum dan sesudah perlakuan pada treatment 1 (0,004), treatment 2 (0,001), treatment 3 (0,032) sedangkan pada kontrol (0,250), berarti tidak terdapat perbedaan bermakna kadar COD sebelum dan sesudah perlakuan. Saran penelitian ini adalah perlu ada penyuluhan dan pelatihan pengolahan limbah sebelum dibuang ke lingkungan untuk mengrangi pencemaran langsung. ABSTRACT Aren palm starch liquid waste is waste that is produced in the process of extracting the palm fiber to get starch flour deposits. The resulting waste contains BOD5 2985 mg / L and COD 8740 mg / L which exceeds the quality standard according to the Central Java Regional Regulation No 5 of 2012. The purpose of this study was to determine the reduction in levels of BOD5 and COD by a combination of aeration filtration and adsorption methods. This type of research is an experiment with the Pretest-Posttest Control Group Design approach. The number of replications used is 4. Data were analyzed using paired T-test. There were no significant differences in BOD5 levels before and after treatment in treatment 1 (0.052), treatment 2 (0.057), treatment 3 (0.138), control (0.964) (p> 0.05). There are significant differences in COD levels before and after treatment in treatment 1 (0.004), treatment 2 (0.001), treatment 3 (0.032) while in control (0.250) means there is no significant difference in COD levels before and after treatment. According to this research, there is a need for counseling and training in waste management before being discharged into the environment to reduce direct pollution.